Parasitic Fauna of Some Freshwater Fishes from Greater Zab River, Kurdistan Region, Iraq - Muhammad, Israa M.; Dhahir, Sara F.; Bilal, Samir J. (Science Journal of University of Zakho, 2013)
A total of 74 fishes, belonging to six species (Barbus grypus, B. kersin, B.  luteus, Cyprinion macrostomum, Cyprinus carpio and Silurus triostegus) were collected from Greater Zab river near Gwer district, southwest Erbil city, Kurdistan region, Iraq, from November 2011 until the end of March 2012. The fishes were examined for ecto- and endoparasites. The study revealed the existence of eight species of parasites which included one species of protozoa (Trichodina mutabilis), three species of monogenean (Dactylogyrus barbuli, Gyrodactylus kherulensis and Paradiplozoon cyprini), metacercaria Diplostomum spathaceum, two species of cestodes (Bothriocephalus acheilognathi and Proteocephalus osculatus) and one species of crustacean (Pseudolamproglena annulata). S. triostegus was regarded as a new host for T. mutabilis and G. kherulensis. Also, B. kersin forD. barbuli and C.  macrostomum for P. cyprini in Iraq.
Keywords: Ecto- endoparasite; Fish; Greater Zab river; Iraq